The Responsibilities of the State to Regulate and Prosecute Business Activities within the Framework of the Inter-American System of Human Rights - Anicama, Cecilia (2009)
The main objective of this article is to show the scope and content of the States parties to the American Convention on Human Rights to regulate and judge business activities. All this in accordance with the reports that present the scope and content of the obligations of the States Parties to regulate and judge the actions of the companies under each of the treaties and on the basis of the comments developed by the treaty bodies. As a result, references will be made to the Inter-American Commission on Human Rights and the Inter-American Court of Human Rights. In the first place, the historical development of the Inter-American Human Rights System will be shown. As a result, the Magna Carta and its articles included are highlighted. Second, the analysis of the Commission's reports on individual cases, precautionary measures and countries will be shown. On the other hand, reference is also made to the case law of the Court regarding the judgments on the merits, the advisory opinions and the resolutions of provisional measures. The analyzed documents cover from the beginning of April 2008. Third, emphasis is placed on highlighting the respect of obligations of the States to regulate, judge and sanction the actions of companies to protect against abuses perpetrated by them. For this reason, the legislation developed, the administrative measures will be shown; and in a second line, the judicialization through the effective remedies and the mechanisms of complaint and reparation. Fourth, the author will present the different areas that require a broader elaboration of the Commission and the Court. Fifth, the recommendations on procedures that could facilitate a more in-depth analysis on the subject of business and human rights are presented. In sum, throughout the text the different decisions that both the Commission and the jurisprudence of the Court issued on the issue of human rights and its relationship with the company will be reviewed.